Impacts of the Invasive Impatiens glandulifera: Lessons Learned from One of Europe’s Top Invasive Species - Coakley, Stephanie (Biology (Basel), 2021)
SIMPLE SUMMARY: Plants and animals are a part of a larger system, commonly referred to as an ecosystem. This generally implies a balance existing between prey and predators. The unintentional introduction of a species in a new environment can lead to a significant alteration of the ecosystem(s) and the uncontrolled spread of the species. When this takes place, the introduced species is referred to as invasive. Invasives can affect the ecosystem in profound ways, and generally, negatively impacting on the native species. This manuscript reviewed the current knowledge of one of Europe’s top invasives, the Himalayan balsam (Impatiens glandulifera). It provides insights on the species and what have we learned from this invasive species. ABSTRACT: Biological invasions are renowned for their negative ecological and economic implications, however from studying invasions invaluable insights can be gained in the fields of ecology and evolution- potentially contributing towards conservation plans to deal, not only with biological invasion, but with other concerning issues, such as climate change. Impatiens glandulifera, or Himalayan balsam, is widely considered to be a highly problematic invasive, having spread across more than thirty countries during the past century. This paper will examine the findings which have arose from studying I. glandulifera and its impacts on the invaded ecosystem.